Role of Farmers’ Personal Values in Soil Fertility Management Decisions: Evidence from Means-End Chain Analysis of Peri-urban Leafy Vegetable Production in Kenya - Okello, Julius J.; Lagervisk, Carl Johan; Ngigi, Marther; Karanja, Nancy (My University, 2012)
Peri-urban areas play a major role in the supply of vegetables consumed in urban areas. In order to meet high demand for aesthetic quality characteristics, peri-urban farmers use intensive production practices characterized by use external inputs. This paper uses Means-End Chain analysis approach to examine the role farmers’ personal values play in the decision to use soil fertility improvement inputs namely, animal manures (organic fertilizer) and inorganic fertilizers. It found that use of animal manures and inorganic fertilizers was driven by the need to earn higher profit margins thus making more money in order to meet family needs. This in turn met farmers’ personal values relating to, among others, happiness, leading a comfortable life, independence and healthy life. The major implication of these findings was that farmers’ private goals could, with the urging of the market that demands unique aesthetic quality characteristics, promote intensive applications of both the organic and inorganic inputs with potential negative environmental consequences.
Keywords: Peri-urban vegetable farmers; Manure and fertilizer use; Personal values; Means-end chain approach